A novel molecularly imprinted polymer sensor for sweat cortisol with embedded probe based on the co-deposition of Prussian Blue and Polypyrrole - Zixuan Song; Minghui Yin; Bo Rui; Tiezhu Liu; Wei Song; Li Sun; Shengmin Li; Jun Wang; Mengdi Han; Guangyang Gou; Ning Xue; Chunxiu Liu (Sensors and Actuators Reports, 2024)
The cortisol in human body is a crucial biomarker in terms of wellness management, mental state monitoring and stress-related disorder diagnosis. Therefore, the rapid, reliable and facile measurement of cortisol concentration has attracted extensive research interest. However, traditional cortisol detection such as immunosensing requires demanding laboratory layout, lengthy procedures and high costs, which means, consequently, it is incompatible with the current goal of cortisol sensing. Given the contradiction, an electrochemical sensor based on molecularly imprinted polymer (MIP) for simple, efficient, non-invasive cortisol detection was proposed. The two-step approach employed is simple enough and allows for the mass production of devices. And the embedding of Prussian Blue (PB) within the MIP layer eliminates the need for complex external probes, thereby making the resultant sensors more suitable for integration into wearable devices. We firstly demonstrated the feasibility of the proposed strategy and characterized the successful formation of cavities specific to cortisol molecules. Thereafter, we measured the dependence of the current response on cortisol concentration in Phosphate Buffered Saline (PBS) buffer, which revealed a near-linear relationship between the logarithm of the cortisol concentration and the redox current from 10−9 mol/L to 10−5 mol/L, covering the optimal range of cortisol concentration in sweat. Subsequently, sensors with the same specifications were prepared and tested in PBS buffer, exhibiting good consistency. In artificial sweat, we further demonstrated that they have benign selectivity, interference immunity and great potential in practical applications.